Extraction kinetics of coals at subcritical and supercritical conditions - Pehlivan, D; Gurkahraman, M; Pamuk, V (Marcel Dekker Inc, 1996)
The extraction kinetics of two lignites and one bituminous coal with benzene, toluene and pyridine were studied at both sub and supercritical conditions in a batch reactor equipped with a coal basket. The time-extract yield data of lignites at supercritical conditions could'nt be treated due to severe thermal decomposition and heating-up effects. The data for Zonguldak coal and those for subcritical extraction of Cizre lignite could be fitted into a first order rate equation with the rate constants changing 0.02-0.05 min(-1) range.